INTERPRETATION OF ENLIGHTENMENT AND SPIRITUALITY - Saidakbarova Muqaddas (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Kokand literary environment is an integral part of Movaraunnahr cultural history. It is distinguished by its uniqueness in form and meaning within the framework of literary studies. The syncretic mixture observed in the spiritual world and creative activ